Copper ion migration inhibitors, pbt composites and methods of making same
Patent Information
- Application Number
- CN202310327928.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-03-30
AI Technical Summary
更重要的是,现有技术均未考虑金属离子(尤其是铜离子)表面迁移扩散的影响,该问题急需解决
[0028]1、本发明的用于PBT树脂的铜离子迁移抑制剂,包括组分A和组分B,其二者协同作用,具有螯合铜离子作用效果明显,耐迁移抽提,持久性好的优势,可极大的抑制铜离子扩散带来的产品漏电流及击穿失效风险。
Smart Images

Figure BDA0004153872670000021 
Figure BDA0004153872670000051 
Figure BDA0004153872670000061
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials, and particularly relates to a copper ion migration inhibitor, a thermoplastic polyester composite material, and a method for preparing the same. Background Technology
[0002] IGBTs (Insulated Gate Bipolar Transistors) are core devices for energy conversion and transmission, commonly known as the "CPU" of power electronic devices, and are widely used in rail transportation, smart grids, aerospace, electric vehicles, and new energy equipment. The internal structure of an IGBT mainly consists of a chip and potting compound, while the external structure is a plastic shell and side frame. Materials used include reinforced PPS, flame-retardant reinforced PPA, and flame-retardant PBT (polybutylene terephthalate). Considering cost-effectiveness, flame-retardant reinforced PBT is currently the primary material used for IGBT shells in new energy vehicles. PBT is a thermoplastic polyester, one of the five major engineering plastics, with good processing and electrical properties. It is resistant to high temperatures, moisture, oil, and chemical corrosion, and is widely used in the electronics, electrical, and automotive industries.
[0003] IGBT modules operate in environments involving high temperature, high humidity, and high voltage, requiring the casing material to maintain good insulation stability under these special conditions. However, under prolonged high temperature and high humidity conditions, some low-molecular-weight substances may leach from flame-retardant reinforced PBT materials. These substances are prone to carbonization, affecting the insulation performance of the product. Simultaneously, the IGBT casing comes into contact with metal components such as busbars. Under prolonged high temperature, high humidity, and high voltage conditions, some metal ions, especially copper ions, are generated. Copper ions, upon contact with acidic substances or water, pose a risk of migration to the casing surface, potentially leading to IGBT module breakdown. Existing technologies have mitigated the leachation of low-molecular-weight substances in flame-retardant reinforced PBT under high temperature and high humidity environments by optimizing the formulation, improving the compatibility of flame retardants with resins, or enhancing the temperature resistance of additives, thus reducing the risk of carbonization and ensuring insulation. However, further reduction of low-molecular-weight substance leachation is necessary. More importantly, existing technologies do not consider the impact of surface migration and diffusion of metal ions (especially copper ions), a problem that urgently needs to be addressed. Summary of the Invention
[0004] The technical problem to be solved by this invention is to overcome the deficiencies and defects mentioned in the background art above, and to provide a copper ion migration inhibitor for PBT resin, a flame-retardant reinforced PBT composite material, and a method for preparing the same. This flame-retardant reinforced PBT composite material with a copper ion migration inhibitor has the advantages of low precipitation under high temperature and high humidity conditions and effective inhibition of metal ion migration. To solve the above technical problem, the technical solution proposed by this invention is as follows:
[0005] A copper ion migration inhibitor for PBT resin includes component A and component B, wherein component A is an acylhydrazine compound and component B is a sulfur-containing phenyl phosphite organic compound, and the mass ratio of component A to component B is 1:(0.5-5).
[0006] In the aforementioned copper ion migration inhibitors, preferably, component A comprises one or more of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, (3,5-di-tert-butyl-4-hydroxyphenyl)propionate oxaloyl(diimino-2,1-ethylidene) ester, N,N'-diacetyl adipate dihydrazine, 1,2-bis(2-hydroxybenzoyl)hydrazine, salicylsalicylic acid hydrazine, and 3-salicylamido-1,2,4-triazole; component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite; and the mass ratio of component A to component B is 1:(1-2).
[0007] In the above-mentioned copper ion migration inhibitors, preferably, component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and the mass ratio of component A to component B is 1:1.
[0008] In this invention, for PBT resin systems, the use of inorganic components as copper ion migration inhibitors can affect the impact toughness of the material. This invention preferably uses organic compounds, which require small amounts and have minimal impact on overall performance. Furthermore, the combination of hydrazide compounds and sulfur-containing phenyl phosphite organic compounds has the advantages of significant copper ion chelation effect, resistance to migration and extraction, and good durability. More preferably, a specific mass ratio of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine and 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite is used, as their synergistic effect is optimal. This combination can greatly suppress leakage current and breakdown failure risks caused by copper ion diffusion, resulting in good durability and minimal impact on the overall performance of the PBT resin system.
[0009] As a general technical concept, the present invention also provides a flame-retardant reinforced PBT composite material, comprising the following raw materials in parts by weight:
[0010]
[0011] The metal ion migration inhibitor is the copper ion migration inhibitor mentioned above.
[0012] In the above-mentioned flame-retardant reinforced PBT composite material, preferably, the viscosity of the PBT resin is 0.8-1.3, and it is produced by the PTA method; the glass fiber is continuous glass fiber.
[0013] In the above-mentioned flame-retardant reinforced PBT composite material, preferably, the flame retardant is an organic phosphonate flame retardant or a composite flame retardant system including a brominated flame retardant and a synergist; the organic phosphonate flame retardant is a Clariant OP series flame retardant (such as Clariant OP1312, OP1314, OP1230, OP1240, OP1400, preferably OP1240); the brominated flame retardant includes brominated polystyrene, brominated epoxy resin, and polydibromostyrene. The synergist comprises one or more of the following: pentabromobenzyl polyacrylate, phenoxytetrabromobisphenol A carbonate oligomer, tris(tribromophenoxy)cyanurate, and 1,2-bis(tetrabromophthalimide) ethane, more preferably a brominated epoxy resin with a molecular weight of around 20,000; the synergist comprises one or more of the following: nano zinc oxide, nano aluminum oxide, barium metaborate, ammonium metaborate, antimony trioxide, antimony pentoxide, sodium pyroantimonate, potassium pyroantimonate, sodium metaantimonate, zinc borate, and zinc stannate.
[0014] In the above-mentioned flame-retardant reinforced PBT composite material, preferably, the raw materials further include 1-5 parts of a toughening agent, wherein the toughening agent includes one or more of the following: ethylene-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, acrylonitrile-ethylene-propylene-butadiene-styrene copolymer, methyl methacrylate-glycidyl methacrylate-ethyl acrylate copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, ethylene-butyl acrylate-maleic anhydride copolymer, methyl acrylate-butadiene-styrene copolymer, ethylene-methyl acrylate copolymer, and ethylene-octene copolymer grafted with maleic anhydride. More preferably, it is one or more of the following: ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, and ethylene-butyl acrylate-maleic anhydride copolymer.
[0015] In the above-mentioned flame-retardant reinforced PBT composite material, preferably, the raw materials further include 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, and 0.1-1 parts of anti-hydrolysis agent; the lubricant is dendritic additive CYD-C600, the antioxidant includes one or more of hindered phenols, phosphites, and organosulfur compounds (preferably a mixture of 1010, PEPQ, and DSTDP), and the anti-hydrolysis agent is carbodiimide. The CYD-C600 used in this invention is specifically for PBT and, in addition to improving flowability, also provides internal and external lubrication; no other lubricating components are added to the system.
[0016] As a general technical concept, the present invention also provides a method for preparing the above-mentioned flame-retardant reinforced PBT composite material, comprising the following steps:
[0017] (1) Mix the metal ion migration inhibitor and part of PBT resin evenly, then add the evenly mixed raw material to a twin-screw extruder for melt extrusion, and then inject it into the impregnation chamber of the glass fiber impregnation die head. After the glass fiber is heated through the glass fiber drying tunnel, it is added to the impregnation mold so that the melt in the impregnation chamber fully covers the glass fiber. Then, it is drawn, cooled, and pelletized to obtain glass fiber reinforced PBT masterbatch; control the pellet length to 1-2 mm.
[0018] (2) Mix the flame retardant and the remaining PBT resin evenly, melt-extrude the mixture through a twin-screw extruder, and granulate it to obtain flame retardant masterbatch; control the granulation length to be 1-2 mm.
[0019] (3) The glass fiber reinforced PBT masterbatch prepared in step (1) is mixed evenly with the flame retardant masterbatch prepared in step (2) to obtain the flame retardant reinforced PBT composite material.
[0020] Specifically, the detailed preparation process includes the following steps:
[0021] ① Mix 20-40 parts PBT resin, 1-5 parts toughening agent, 0.05-0.5 parts antioxidant, 0.1-1 parts metal ion migration inhibitor, and 0.1-1 parts lubricant evenly;
[0022] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion, and then inject them into the impregnation chamber of the glass fiber impregnation die head. After heating 20-40 parts of continuous glass fiber through the glass fiber drying tunnel, add them to the impregnation die, so that the melt in the impregnation chamber fully covers the glass fiber. Then, draw, cool, and pelletize to obtain glass fiber reinforced PBT masterbatch with a glass fiber mass fraction of 50-60%; control the pellet length at 1-2 mm.
[0023] ③ Mix 10-20 parts of flame retardant, 0.05-0.5 parts of antioxidant and the remaining PBT resin evenly, melt extrude through a twin-screw extruder, and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0024] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0025] In the above preparation method, preferably, in step (1), the operating temperature of the twin-screw extruder is 220-270℃, the operating temperature of the melt pump is 240-280℃, the operating temperature of the impregnation die is 240-270℃, the temperature of the glass fiber drying tunnel is 100-150℃, and the density of the prepared glass fiber reinforced PBT masterbatch is 1.5-1.8 g / cm³. 3 In step (2), the operating temperature of the twin-screw extruder is 210-250℃.
[0026] The flame-retardant reinforced PBT composite material of this invention is particularly suitable for IGBTs used in new energy vehicles, and is especially suitable for preparing IGBT module shells. It offers advantages such as low precipitation in high-temperature and high-humidity environments, effective suppression of copper ion migration risk, high strength and toughness, excellent molding appearance, and simple preparation. Specifically, flame-retardant reinforced PBT composite materials precipitate low-molecular-weight substances under high-temperature and high-humidity conditions, affecting the product's insulation performance. This invention's flame-retardant reinforced PBT composite material uses polymeric components with high thermal stability and low free bromine content, or Clariant OP series flame retardants, without using easily migrating lubricants, and adds dendritic lubricating additives. This controls the precipitation of low-molecular-weight substances such as flame retardants, lubricants, and antioxidants under high-temperature and high-humidity conditions, effectively controlling surface carbonization of the IGBT shell in the usage environment, reducing the risk of CTI-induced failure. After 1000 hours at 85°C and 85% humidity, no obvious precipitates are observed on the product surface. IGBT shells come into contact with metal busbars, and in high-temperature and high-humidity environments, there is a risk of copper ion diffusion and migration, which can lead to leakage current or breakdown. The flame-retardant reinforced PBT material of this invention contains an inhibitor that chelates copper particles, controlling copper ion diffusion and migration. Even in high-temperature, high-humidity, and copper-corrosion environments, no free copper ions are detected on the product surface. Traditional production of reinforced flame-retardant PBT composites typically involves twin-screw extrusion granulation followed by injection molding. This process easily causes decomposition of flame retardants or additives under high shear heat conditions, exacerbating the risk of precipitation. Simultaneously, the glass fiber length is unevenly dispersed after shearing and difficult to control, leading to product warping and low strength. The preparation method of this invention uses a blending injection molding method with flame-retardant masterbatch and fiber masterbatch, reducing the thermal decomposition caused by the simultaneous twin-screw extrusion of flame retardants and glass fiber, thus reducing precipitation on the product surface. The prepared masterbatch has a relatively uniform density, facilitating physical mixing and simplifying the material preparation process. It effectively controls the length and distribution of glass fiber, resulting in better performance, stable and reliable product performance, a narrower glass fiber length distribution in the injection molded product, and excellent product rigidity. The surface of flame-retardant reinforced PBT composite material is severely floating with fibers after injection molding, which affects the appearance. Even white products will show differences. This invention adds dendritic compounds, which improves the material flowability, reduces floating fibers, and results in a good product appearance with no obvious glass fiber agglomeration.
[0027] Compared with the prior art, the advantages of the present invention are as follows:
[0028] 1. The copper ion migration inhibitor for PBT resin of the present invention includes component A and component B. The two components work synergistically to have the advantages of significant chelation effect on copper ions, resistance to migration extraction, and good durability. It can greatly suppress the product leakage current and breakdown failure risk caused by copper ion diffusion.
[0029] 2. The flame-retardant reinforced PBT composite material of the present invention solves the risk of leakage current and breakdown failure caused by copper ion diffusion in the electrode under high temperature, high humidity and high pressure conditions by adding copper ion migration inhibitors, thereby improving the reliability and stability of the product.
[0030] 3. The flame-retardant reinforced PBT composite material of the present invention has high rigidity, high toughness, excellent electrical properties and molding and processing performance, and is suitable for the production of IGBT module shells for new energy vehicles.
[0031] 4. The preparation method of the flame-retardant reinforced PBT composite material of the present invention adopts the injection molding method of blending flame-retardant masterbatch and glass fiber reinforced PBT masterbatch. This can ensure that the decomposition of flame retardant is reduced, the length and distribution of glass fiber are effectively controlled, and the performance of injection molded products is better. Detailed Implementation
[0032] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0033] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0034] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0035] Example 1:
[0036] A copper ion migration inhibitor for PBT resin includes component A, wherein component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.
[0037] The flame-retardant reinforced PBT composite material of this embodiment contains raw materials with the following parts by weight as shown in Table 1 below.
[0038] Table 1: Raw material composition of flame-retardant reinforced PBT composite materials in Examples 1-7 and Comparative Examples 1-3
[0039]
[0040]
[0041] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0042] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.1 parts N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0043] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0044] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0045] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0046] Example 2:
[0047] A copper ion migration inhibitor for PBT resin includes component B, which is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite.
[0048] The flame-retardant reinforced PBT composite material of this embodiment includes raw materials with the weight parts of the components shown in Table 1 above.
[0049] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0050] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.1 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0051] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0052] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0053] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0054] Example 3:
[0055] A copper ion migration inhibitor for PBT resin comprises component A and component B, wherein component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, and the mass ratio of component A to component B is 1:1.
[0056] The flame-retardant reinforced PBT composite material of this embodiment includes raw materials with the weight parts of the components shown in Table 1 above.
[0057] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0058] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.05 parts N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 0.05 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0059] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0060] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0061] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0062] Example 4:
[0063] A copper ion migration inhibitor for PBT resin comprises component A and component B, wherein component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, and the mass ratio of component A to component B is 1:1.
[0064] The flame-retardant reinforced PBT composite material of this embodiment includes raw materials with the weight parts of the components shown in Table 1 above.
[0065] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0066] ① Mix 29 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.05 parts N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 0.05 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0067] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0068] ③ Mix 20 parts of flame retardant OP 1240, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 17 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0069] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT special material.
[0070] Example 5:
[0071] A copper ion migration inhibitor for PBT resin comprises component A and component B, wherein component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, and the mass ratio of component A to component B is 1:2.
[0072] The flame-retardant reinforced PBT composite material of this embodiment includes raw materials with the weight parts of the components shown in Table 1 above.
[0073] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0074] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.033 parts N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 0.067 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0075] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0076] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0077] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0078] Example 6:
[0079] A copper ion migration inhibitor for PBT resin comprises component A and component B, wherein component A is N,N'-diacetyl adipate dihydrazide and component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, and the mass ratio of component A to component B is 1:2.
[0080] The flame-retardant reinforced PBT composite material of this embodiment includes raw materials with the weight parts of the components shown in Table 1 above.
[0081] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0082] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.033 parts N,N'-diacetyl adipate dihydrazide, 0.067 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0083] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0084] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0085] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0086] Example 7:
[0087] A copper ion migration inhibitor for PBT resin comprises component A and component B. Component A is a mixture of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine and N,N'-diacetyl adipate dihydrazine in a mass ratio of 1:1. Component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, and the mass ratio of component A to component B is 1:1.
[0088] The flame-retardant reinforced PBT composite material of this embodiment includes raw materials with the weight parts of the components shown in Table 1 above.
[0089] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0090] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.025 parts N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 0.025 parts N,N'-diacetyl adipate dihydrazine, 0.05 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0091] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0092] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0093] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0094] Comparative Example 1:
[0095] A copper ion migration inhibitor for PBT resin comprises component A and component B, wherein component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, and the mass ratio of component A to component B is 1:1.
[0096] The flame-retardant reinforced PBT composite material of this comparative example includes raw materials comprising the parts by weight of the components shown in Table 1 above.
[0097] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0098] ① Mix 49 parts PBT resin, 3 parts toughening agent PTW, 0.2 parts antioxidant 1010, 0.1 parts antioxidant PEPQ, 0.05 parts N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 0.05 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, 0.2 parts carbodiimide, 13 parts flame retardant brominated epoxy, and 4 parts flame retardant synergist antimony trioxide evenly;
[0099] ② Add the uniformly mixed raw materials from step ① to a conventional twin-screw extruder for melt extrusion (temperature set at 230±20℃). Add 30 parts of continuous glass fiber HMG836 through the natural venting hole, and then traction pelletize to prepare a flame-retardant reinforced PBT composite material with a length of about 3mm.
[0100] Comparative Example 2:
[0101] The flame-retardant reinforced PBT composite material of this comparative example includes raw materials comprising the parts by weight of the components shown in Table 1 above.
[0102] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0103] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0104] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0105] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19.1 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0106] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0107] Comparative Example 3:
[0108] A copper ion migration inhibitor for PBT resin comprises component A and component B, wherein component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, and the mass ratio of component A to component B is 3:1.
[0109] The flame-retardant reinforced PBT composite material of this comparative example includes raw materials comprising the parts by weight of the components shown in Table 1 above.
[0110] The preparation method of the above flame-retardant reinforced PBT composite material includes the following steps:
[0111] ① Mix 30 parts PBT resin, 3 parts toughening agent PTW, 0.1 parts antioxidant 1010, 0.05 parts antioxidant PEPQ, 0.075 parts N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 0.025 parts 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1”-phosphite, 0.4 parts CYD-C600, and 0.2 parts carbodiimide evenly;
[0112] ② Add the uniformly mixed raw materials from step ① to a twin-screw extruder for melt extrusion at an extruder temperature of 250±10℃. Then inject the mixture into the impregnation chamber of the glass fiber impregnation die head at a temperature of 260±10℃. After heating 30 parts of continuous glass fiber HMG836 through a glass fiber drying tunnel (temperature set at 120±10℃), add it to the impregnation die to ensure that the melt in the impregnation chamber fully coats the glass fiber. Then, draw, cool, and pelletize to obtain reinforced PBT masterbatch with a glass fiber mass fraction of 50±3%; control the pellet length at 1.5±0.3mm.
[0113] ③ Mix 13 parts of flame retardant brominated epoxy, 4 parts of flame retardant synergist antimony trioxide, 0.1 parts of antioxidant 1010, 0.05 parts of antioxidant PEPQ and the remaining 19 parts of PBT resin evenly, melt extrude through a conventional twin-screw extruder (temperature set at 230±20℃), and pelletize to obtain flame retardant masterbatch with density and length similar to glass fiber reinforced PBT masterbatch;
[0114] ④ Mix the glass fiber reinforced PBT masterbatch prepared in step ② with the flame retardant masterbatch prepared in step ③ evenly to obtain the flame retardant reinforced PBT composite material.
[0115] The performance of the flame-retardant reinforced PBT composite materials prepared in Examples 1-7 and Comparative Examples 1-3 was tested, and the results are shown in Table 2 below.
[0116] Table 2: Performance data of flame-retardant reinforced PBT composite materials prepared in Examples 1-7 and Comparative Examples 1-3
[0117]
Claims
1. A flame-retardant reinforced PBT composite material, characterized in that, Including the following parts by weight of raw materials: 40-60 parts of PBT resin; 20-40 parts glass fiber; 10-20 parts flame retardant; Metal ion migration inhibitor 0.1-1 part; The metal ion migration inhibitor comprises component A and component B, wherein component A is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and component B is 2-(1,1-dimethylethyl)-4-[[5-(1,1-dimethylethyl)-4-hydroxy-2-methylphenyl]thio]-5-methylphenol-1,1',1''-phosphite, and the mass ratio of component A to component B is 1:1; The preparation method of the flame-retardant reinforced PBT composite material includes the following steps: (1) Mix the metal ion migration inhibitor and part of PBT resin evenly, then add the evenly mixed raw material to a twin-screw extruder for melt extrusion, and then inject it into the impregnation chamber of the glass fiber impregnation die head. After heating the glass fiber through the glass fiber drying tunnel, add it to the impregnation mold so that the melt in the impregnation chamber fully covers the glass fiber. Then draw, cool, and granulate to obtain glass fiber reinforced PBT masterbatch; control the granulation length to 1-2 mm. (2) Mix the flame retardant and the remaining PBT resin evenly, melt-extrude the mixture through a twin-screw extruder, and granulate it to obtain flame retardant masterbatch; control the granulation length to be 1-2 mm; (3) Mix the glass fiber reinforced PBT masterbatch prepared in step (1) with the flame retardant masterbatch prepared in step (2) evenly to obtain the flame retardant reinforced PBT composite material.
2. The flame-retardant reinforced PBT composite material according to claim 1, characterized in that, The PBT resin has a viscosity of 0.8-1.3 and is produced by the PTA method; the glass fiber is continuous glass fiber.
3. The flame-retardant reinforced PBT composite material according to claim 1, characterized in that, The flame retardant is an organic phosphonate flame retardant or a composite flame retardant system including a brominated flame retardant and a synergist; the organic phosphonate flame retardant is Clariant OP series flame retardant; the brominated flame retardant includes one or more of brominated polystyrene, brominated epoxy resin, polydibromostyrene, pentabromobenzyl polyacrylate, phenoxytetrabromobisphenol A carbonate oligomer, tris(tribromophenoxy)cyanurate, and 1,2-bis(tetrabromophthalimide) ethane; the synergist includes one or more of nano zinc oxide, nano alumina, barium metaborate, ammonium metaborate, antimony trioxide, antimony pentoxide, sodium pyroantimonate, potassium pyroantimonate, sodium metaantimonate, zinc borate, and zinc stannate.
4. The flame-retardant reinforced PBT composite material according to any one of claims 1-3, characterized in that, The raw materials also include 1-5 parts of toughening agent, which includes one or more of the following: ethylene-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, acrylonitrile-ethylene-propylene-butadiene-styrene copolymer, methyl methacrylate-glycidyl methacrylate-ethyl acrylate copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, ethylene-butyl acrylate-maleic anhydride copolymer, methyl acrylate-butadiene-styrene copolymer, ethylene-methyl acrylate copolymer, and ethylene-octene copolymer grafted with maleic anhydride.
5. The flame-retardant reinforced PBT composite material according to any one of claims 1-3, characterized in that, The raw materials also include 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, and 0.1-1 parts of anti-hydrolysis agent; the lubricant is dendritic additive CYD-C600, the antioxidant includes one or more of hindered phenols, phosphites and organosulfurs, and the anti-hydrolysis agent is carbodiimide.
6. The flame-retardant reinforced PBT composite material according to claim 1, characterized in that, In step (1), the operating temperature of the twin-screw extruder is 220-270℃, the operating temperature of the impregnation die is 240-270℃, the temperature of the glass fiber drying tunnel is 100-150℃, and the density of the prepared glass fiber reinforced PBT masterbatch is 1.5-1.8 g / cm³. 3 In step (2), the operating temperature of the twin-screw extruder is 210-250℃.
Citation Information
Patent Citations
A halogen free flame retardant long glass fiber reinforced PBT composite material and a preparation method thereof
CN103160080A
Extrusion grade polypropylene material with high heat resistance and method for preparing extrusion grade polypropylene material
CN109575434A
Low-warpage, damp-heat-aging-resistance high-pressure-resistant flame-retardant polyester material and preparation method
CN112852125A
Multilayer resin sheet and resin-sheet laminate
EP2641736A1